MENGUNGKAP RELASI KAPITALISME, DEMOKRASI DAN GLOBALISASI (KAJIAN DALAM PERSPEKTIF STUDI HUKUM KRITIS) - FX Adji Samekto (Faculty of Law, Universitas Jenderal Soedirman, 2014)
There is a strong relationship among capitalism, democracy and globalization. Jurists of the nine-teenth century have sought to create a legal structure that based on the idea of democracy and the free market, commitment to a democratic republic and the market system as required components of republic. Thus there is a kind of mutualism symbiosis between the demands of the enactment of democratic system and free market mechanisms. Accordingly, globalization, as a new form of capitalist expansion will be running well in any region in which democracy grows.Key words: capitalism, democracy, globalization, critical legal studies